Relationships between neuroscience and Physics teaching in the brazilian context: A systematic review (Research, Society and Development, 2024)
A branch that is still little explored in the field of research in education is neuroscience. This area of research aims to understand how the process of acquiring and using knowledge occurs through the study of neural mechanisms. In this study, we intend to analyze the potential of the theoretical-methodological framework of neuroscience for education as a new path for research in Physics teaching, as it reveals interesting and innovative possibilities for investigating old problems known in the area. In this sense, we find ourselves faced with the following research problem: what are the contributions of interface research between cognitive neuroscience and Physics teaching? To this end, the proposal is to investigate how these relationships are approached in the Brazilian context based on a systematic literature review, covering the last 10 years. The research returned the following main results: i) the inclusion of neurosciences in the initial training curricula of Physics teachers; ii) the relationships between Piaget's theory and Cognitive neuroscience in Physics teaching; iii) dissemination of what has been produced in terms of research on neuroscience and Physics teaching; and, also, iv) an interdisciplinary approach to teaching Physics. It is expected that this study will seek to understand how the teaching-learning process develops at a neurological level with the aim of improving teaching practice and that the fruits of this investigation will encourage the development of future projects.